(untitled) (Південний архів (історичні науки), 2023)
Purpose. On the basis of a comprehensive analysis of the work of rural cultural and educational institutions in the postwar period (1943–1950), the purpose is to show the essence and character of the ideological influence on them. Methods. The architectonics of the research is based on the problem-chronological method. Results. The article comprehensively analyzes the system of ideological influence on the work of rural cultural and educational institutions. The practice of party control over the work of rural cultural and educational institutions and the use of various forms of ideological influence on the consciousness of the villagers are revealed. It was found that the cultural and educational processes in the rural areas of the regions of Ukraine were marked by strict censorship and the subordination of all forms and methods of working with people to the tasks of the ruling communist ideology at the time, which allows to determine the state policy in the field of rural culture in 1943–1950s as excessively politicized. Rural cultural and educational institutions were used as strongholds of the mass-political work of Communist Party organizations, promoting the party’s decisions and line, while diverting employees and activists of clubs and libraries from organizing people’s artistic creativity and leisure time. Under the pressure of local power structures, political education circles, agitation collectives, agitation-art brigades and other links of mass-political work, not characteristic of the activities of cultural institutions, were created on the basis of rural cultural and educational institutions. Cultural workers, together with other strata of the rural intelligentsia, were constantly involved in the agitation and propaganda campaigns carried out permanently by party organizations. Conclusions. According to the results of the study of the peculiarities of the cultural and educational processes that took place in the post-war Ukrainian village, it has been concluded that they were characterized by the strengthening of the ideologization of the entire spiritual life of the rural population. Then ruling Communist Party ideology was not limited to subordinating cultural and educational work of clubs and library institutions to its tasks, but also extended to other means of ideological influence on people’s consciousness – oral political agitation, the press, radio and cinema.